Method for the detection of significant bacteriuria in large groups of patients - Leigh, D. A. (1964)
A measured area of blotting paper was used as a vehicle for transferring a constant aliquot of urine on to the surface of a culture medium. The number of bacterial colonies growing in the inoculum area of the medium corresponded to the number of organisms in the urine. One thousand, two hundred and seventy-five urines from women attending an ante-natal clinic were tested by this method, and the results compared with the results of quantitative bacterial counting and of triphenyl tetrazolium chloride (T.T.C.) tests. The method was found to be a simple, cheap, and reliable way of screening urine specimens for significant bacteriuria.